Early revisions of the Femoro-Patella Vialla joint replacement. - Williams, D; Pandit, H; Athanasou, N; Murray, D; Gibbons, C (2013)
The aim of this study was to review the early outcome of the Femoro-Patella Vialla (FPV) joint replacement. A total of 48 consecutive FPVs were implanted between December 2007 and June 2011. Case-note analysis was performed to evaluate the indications, operative histology, operative findings, post-operative complications and reasons for revision. The mean age of the patients was 63.3 years (48.2 to 81.0) and the mean follow-up was 25.0 months (6.1 to 48.9). Revision was performed in seven (14.6%) at a mean of 21.7 months, and there was one re-revision. Persistent pain was observed in three further patients who remain unrevised. The reasons for revision were pain due to progressive tibiofemoral disease in five, inflammatory arthritis in one, and patellar fracture following trauma in one. No failures were related to the implant or the technique. Trochlear dysplasia was associated with a significantly lower rate of revision (5.9% vs 35.7%, p = 0.017) and a lower incidence of revision or persistent pain (11.8% vs 42.9%, p = 0.045). Focal patellofemoral osteoarthritis secondary to trochlear dysplasia should be considered the best indication for patellofemoral replacement. Standardised radiological imaging, with MRI to exclude overt tibiofemoral disease should be part of the pre-operative assessment, especially for the non-dysplastic knee.